2003
DOI: 10.1088/0029-5515/43/8/311
|View full text |Cite
|
Sign up to set email alerts
|

Increased understanding of the dynamics and transport in ITB plasmas from multi-machine comparisons

Abstract: Our understanding of the physics of internal transport barriers (ITBs) is being furthered by analysis and comparisons of experimental data from many different tokamaks worldwide. An international database consisting of scalar and 2-D profile data for ITB plasmas is being developed to determine the requirements for the formation and sustainment of ITBs and to perform tests of theory-based transport models in an effort to improve the predictive capability of the models. Analysis using the database indicates that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…It has also been demonstrated that reversal of magnetic shear by use of current modification by lower hybrid current drive 7 or electron cyclotron current drive 8 encourages ITB development. These are thought to occur when the effects of pressure profile gradient driven instabilities are reduced by the introduction of rotational shear into the unstable region or by providing a region of reversed magnetic shear 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that reversal of magnetic shear by use of current modification by lower hybrid current drive 7 or electron cyclotron current drive 8 encourages ITB development. These are thought to occur when the effects of pressure profile gradient driven instabilities are reduced by the introduction of rotational shear into the unstable region or by providing a region of reversed magnetic shear 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The transport barrier formation near the low-order rational tori found numerically in Hamiltonian systems perturbed by a weak turbulent field at the large Kubo numbers, probably, may have some sort of relation to the transport barriers in fusion experiments (see, e.g., a review [4]). As was mentioned above there is a possible relation between the density of rational magnetic surfaces (or tori) and the transport of particles and energy, particularly, the transport barrier formation in fusion experiments, which has been already discussed in a number of papers [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Unlike qualitative arguments given in those works we have explicitly shown the formation of transport barriers in Hamiltonian systems by direct numerical calculations and explored the conditions at which such barriers are created.…”
Section: Discussionmentioning
confidence: 90%
“…7 in the whole region 0 < J < 1 for the large Kubo number K = 100 (a) and in the region 0.5 < J < 0.55 located near the rational tori ω = 1/3 for the several values of K = 1,2,5, and 100 (b). The values for the other parameters are chosen: q 0 = 0.8, q a = 5, γ ≡ 1, 20 n 50, and α = 5/6, which corresponds to the power spectrum |H mn | 2 ∼ n −5/3 , and the 1 The existence of gaps in the density of rational tori has been pointed out already in many above-mentioned works [15][16][17][18][19][20][21][22][23][24][25], however, no quantitative estimations have been presented. Moreover, I could not find the results obtained here in existing literature, although one could expect that this problem has been treated already in number theory or in other fields of physics.…”
Section: A Monotonic Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Scalings of turbulent diffusion in both CSDX and larger devices characterized by higher temperature follow the same trend. 46,47 When the axial to azimuthal flow coupling is weak, the axial flow is mainly driven by the turbulent Reynolds stress, particularly by the parallel residual part. The reduced 4-field model can thus be simplified to a 2-field predator-prey model which evolves v y and n. In CSDX, probe measurements show that the magnitude of v z is moderate, and that the parallel Reynolds power is much less than that in the perpendicular direction.…”
Section: Discussionmentioning
confidence: 99%